2022
DOI: 10.21203/rs.3.rs-1495332/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring lived experience of recovery processes in those with schizophrenia: A systematic review with thematic synthesis of qualitative evidence

Abstract: The purpose of the study was to conduct a systematic review of literature which explores lived experiences of the manifestation, appearance of meaning, and interpretation of the recovery process in schizophrenia. Recovery as a lived experience in schizophrenia is an idiosyncratic and debated process that emerges from the perspectives of people who experience schizophrenia. Recovery literature is gained from qualitative accounts and synthesising these accounts provides an overview of the evidence base for recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…As such, there is value in further demonstrating that people who have historically had little agency have also facilitated their own recovery (12). Furthermore, in line with previous qualitative studies we found that the participants' recovery process did not primarily occur within specialized mental health services, but in their everyday lives (15,24,27,39,50).…”
Section: Discussionsupporting
confidence: 91%
“…As such, there is value in further demonstrating that people who have historically had little agency have also facilitated their own recovery (12). Furthermore, in line with previous qualitative studies we found that the participants' recovery process did not primarily occur within specialized mental health services, but in their everyday lives (15,24,27,39,50).…”
Section: Discussionsupporting
confidence: 91%